1995
DOI: 10.1111/j.1745-4522.1995.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Chloride Effects on Tba Values of Cooked Meat

Abstract: Ground chicken breast and beef top round (semimembranosus) muscles were treated with CaCl2 (0.05, 0.10, 0.15, and 0.20% on final sample weight basis) and cooked to an internal temperature of 80C. Cooked samples were aerobically stored at 4C for 0 or 4 days and analyzed for 2‐thiobarbituric acid (TBA)‐reactive substances. Results indicated that CaCl2 can either inhibit or accelerate lipid oxidation in cooked meat depending on its concentration/meat animal species. TBA values of chicken samples were decreased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(12 reference statements)
2
1
0
Order By: Relevance
“…Previous studies have suggested that low concentrations of Ca 2+ are able to release the Fe 2+ bound to negatively charged lipid groups, increasing the catalytically active Fe 2+ , thereby stimulating the Fenton reaction. Consistent with this, chicken and beef muscle that had been injected with calcium chloride and cooked, showed increased TBARS when calcium chloride was added at the lower doses (0.05% for chicken; 0.05%, 0.1%, and 0.15% for beef), whereas higher doses decreased lipid oxidation (Cho and Rhee 1995). Injection of beef with calcium chloride (0.12%, 0.24%, and 0.36%) and calcium lactate (0.24%, 0.48%, and 0.72%) accelerated lipid oxidation, whereas calcium ascorbate (0.43%, 0.86%, and 1.29%) inhibited lipid oxidation (Lawrence and others 2003).…”
Section: Interactions With Dietary Compounds That Affect Oxidation Dusupporting
confidence: 65%
“…Previous studies have suggested that low concentrations of Ca 2+ are able to release the Fe 2+ bound to negatively charged lipid groups, increasing the catalytically active Fe 2+ , thereby stimulating the Fenton reaction. Consistent with this, chicken and beef muscle that had been injected with calcium chloride and cooked, showed increased TBARS when calcium chloride was added at the lower doses (0.05% for chicken; 0.05%, 0.1%, and 0.15% for beef), whereas higher doses decreased lipid oxidation (Cho and Rhee 1995). Injection of beef with calcium chloride (0.12%, 0.24%, and 0.36%) and calcium lactate (0.24%, 0.48%, and 0.72%) accelerated lipid oxidation, whereas calcium ascorbate (0.43%, 0.86%, and 1.29%) inhibited lipid oxidation (Lawrence and others 2003).…”
Section: Interactions With Dietary Compounds That Affect Oxidation Dusupporting
confidence: 65%
“…Thus, the overriding prooxidant activity maybe due to the chloride ion of salts. The results obtained for chloride salts in our study were in agreement with results presented by Rhee et al (1983a, b) and Cho and Rhee (1995) for NaCl, KCl, and MgCl 2 in ground pork systems.…”
Section: Resultssupporting
confidence: 96%
“…Lesser values of TBA may be observed due to lipid removal especially heme proteins and oxidative components from mince. Addition of calcium chloride may lead to lowered TBA values (Cho and Rhee 1995). Lipid peroxidation is a complex process.…”
Section: Resultsmentioning
confidence: 99%